Management Models in SMEs, Strategic Tool in Business Management - L. R. Fiallos Ortega; F. F. Esparza Paz; A. G. Castelo Salazar (ESPOCH Congresses)
The business sector constitutes an engine for the Ecuadorian economy through the generation of employment and redistribution of wealth. Therefore, given the current economic dynamics of high competition, globalization of markets, and use of information and communication technologies, business managers need to use different tools such as management models to achieve acceptable levels of utility, profitability, customer satisfaction and permanence in the consumer market. This research involved an analysis of the impact on corporate management of applying different management models of Small and Medium Enterprises (SMEs) in the city of Riobamba, province of Chimborazo (Ecuador). The study was descriptive, cross-sectional, exploratory and non-experimental and it was conducted in the first half of 2019. Data were collected through field investigation and the application of a structured survey with a sample composed of 136 managers, owners and administrators, from a population of 440 entrepreneurs. The results showed that 93% of entrepreneurs knew about the existence of management models, and 41% recorded that total quality is the most applied model followed by continuous improvement (18%) and re-engineering (13%). We conclude that entrepreneurs consider management models to be crucial in the management of their company.